Apathy is associated with poorer abstinence self-efficacy in individuals with methamphetamine dependence. (June 2021) - Hussain, Mariam A.; Iudicello, Jennifer E.; Morgan, Erin E.; Kamat, Rujvi; Heaton, Robert K.; Grant, Igor; ,
Highlights: Used an apathy composite T -score approach validated in methamphetamine-dependence. Apathy, above other factors, associated with poorer drug abstinence self-efficacy. Methamphetamine use characteristics unrelated to drug abstinence self-efficacy. Social peer pressure was riskiest situation for potential methamphetamine relapse. Abstract: Background: Confidence in one's ability to achieve and maintain drug abstinence (i.e., abstinence self-efficacy) is a strong predictor of substance use treatment outcomes. Neurobehavioral factors that may interfere with abstinence self-efficacy are less well established, particularly in methamphetamine (METH). This study investigated whether apathy, which is highly prevalent during active METH use and periods of abstinence, influences abstinence self-efficacy among METH dependent individuals. Methods: Sixty-six participants with lifetime METH dependence and METH abuse/METH dependence diagnoses within the last 18 months (mean age [SD] = 39.5 years [10.7]), and no severe psychiatric or neurological diseases, completed the Methamphetamine Self-Efficacy Scale (MSES), alongside a comprehensive neurobehavioral evaluation. The MSES presents six situations that may lead to relapse and collects self-report ratings for two subscales: "Confidence" (i.e., confidence in one's ability to abstain from using METH, or METH abstinence self-efficacy) and "Temptation" (i.e., how tempted one is to use METH) with regard to each situation. Apathy was measured using a composite T -score comprised of items and scales from three well-validated, self-report assessments. Results: Multivariable linear regression found that higher Apathy T -scores were significantly associated with lower Confidence ratings (i.e., poorer METH abstinence self-efficacy; p  < .05), independent of potentially relevant factors (e.g., Temptation to use METH, comorbid HIV disease, and neurocognitive impairment). Conclusions: Elevated apathy may adversely impact one's confidence to abstain from METH use. Findings highlight the importance of addressing apathy in order to improve METH abstinence self-efficacy, which may subsequently increase the likelihood of successful METH treatment outcomes.